On St Margaret Street - Sophie Nield (Law Text Culture, 2010)
It is not unusual to hear events in public space, be they state-sponsored or resistant, described as ‘pure theatre’, ‘political drama’ or ‘political theatre’. Historically, discussion of political events in public space has often started from the premise that they are ‘theatrical’ because they share attributes with conventional theatre practice – because they use actors, props, scenery, narratives. Certainly, events such as rallies, military parades and demonstrations are ‘theatre-like’ to the extent that they are concerned with concepts and ideas not otherwise materially present, they are organised around the symbolic production of meaning, and they are ‘stage-managed’ in order to be read. Yet it seems to me that the ‘theatrical’ must be expanded as a category both in order to permit a politicised and serious engagement with public events from a theatrical perspective, and also to defend the theatre itself from marginalisation. As soon as the ranks break, the teargas explodes, as soon as damage is done – as soon as anything really happens – it is no longer called ‘pure theatre’ or ‘political drama’.